CompARch: Integrated Augmented Reality Computer Architecture Learning App - Zulkalam, Muhammad Farhan; Mohd Arshad, Muhammad Amri; Nik Mohd Kamaruzaman, Nik Mohd Nasrul Hakimi; Jamalullail, Harith Hakimi; Soosay Nathan, Shelena (Multidisciplinary Applied Research and Innovation, 2026)
This report discusses the development of an application with integrated Augmented Reality (AR) that is designed to help students learn about computer architecture. Many students find it hard to understand complex concepts using traditional teaching methods, which often rely on textbooks and flat diagrams. The AR application aims to provide interactive 3D models of computer components, making learning more engaging. The project followed a structured approach called the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Initial testing showed that students who used the AR application reported better understanding and increased interest in the subject. The report concludes that AR technology can improve learning in the computer architecture subject and suggests further work to enhance the application and expand its content.